Self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete applicable to power transmission tower footing and preparation method of self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete

By using silica hybrid shell microcapsules in the transmission tower base concrete, the capsule core contains expansion agent, adhesive and healing agent, which solves the problem that it is difficult to achieve self-healing function in the prior art, and realizes independent repair and strength recovery when stress or corrosion, effectively preventing structural damage.

CN119898986APending Publication Date: 2025-04-29STATE GRID GANSU ELECTRIC POWER CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411873196.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to achieve self-repair functions in transmission tower foundation concrete that simultaneously has the ability to quickly fill gaps and effectively restore strength, especially lacking effective solutions for problems such as salted soil corrosion and wind load fatigue.

Method used

Silica hybrid shell microcapsules are used, the capsule wall is composed of fume, ethyl cellulose, styrene and polyionic liquid. The capsule core contains microcrystalline cellulose, sodium silicate, silicate cement, magnesium oxide, methyl cellulose and methyl methacrylate monomers. The microcapsules are damaged when stressed or corroded, releasing expansion agents, adhesives and healing agents to fill cracks and restore strength.

Benefits of technology

It realizes the independent repair of cracks in the concrete of the transmission tower foundation, fills gaps, restores strength, and effectively prevents salted soil corrosion and wind load fatigue, extending the service life of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898986A_ABST
    Figure CN119898986A_ABST
Patent Text Reader

Abstract

The invention discloses self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for a power transmission tower footing and a preparation method thereof.The microcapsule concrete comprises conductive concrete and a silicon dioxide hybrid shell microcapsule, and the silicon dioxide hybrid shell microcapsule comprises a capsule wall and a capsule core; the capsule core is prepared from the following raw materials: microcrystalline cellulose, sodium silicate, Portland cement, magnesium oxide, methyl cellulose, a methyl methacrylate monomer and distilled water; the capsule wall is a silicon dioxide hybrid shell and is prepared from the following raw materials: ethyl cellulose, styrene, polyion liquid and silica fume; the surface of the capsule wall is coated with a triethyl boron coating. The self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete disclosed by the invention can realize an intelligent self-repairing function, can be timely damaged when being subjected to stress or corrosive ions, not only can recover the strength of a material, but also can fill gaps and improve the permeability of the material so as to prevent external corrosive substances from invading.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a self-repairing conductive concrete microcapsule concrete and a preparation method thereof, and in particular to a self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for a transmission tower base and a preparation method thereof. Background Art

[0002] Once concrete microcracks are formed, it is difficult to detect and repair them by conventional methods before they develop, condense, and grow into large cracks, which poses a major threat to the performance and service life of concrete. Due to the complex natural environment conditions in the northwest region, the structure is required to be able to effectively prevent the entry of corrosive substances after the cracks appear and maintain the structural performance. At the same time, since most power transmission and transformation projects are located in remote areas and difficult to monitor and maintain, the structure is required to have good long-term serviceability and be able to maintain strength for a long time. Therefore, the self-healing microcapsules used in power transmission and transformation projects should have both of the above-mentioned properties, that is, quickly filling gaps and effectively restoring strength. In order to meet these two requirements, it is necessary to develop new self-healing microcapsules. At present, the conductive phase of common conductive concrete mostly uses graphite, carbon nanotubes, carbon powder, metal powder, etc. However, the poor cohesion between graphite and cement slurry leads to a sharp decrease in the strength of concrete; carbon powder has no effect on the strength of concrete; carbon fiber is not easy to disperse in concrete and is easy to agglomerate, thereby reducing the strength of concrete. In addition, the existing types of microcapsules can only fill cracks or restore strength, and cannot meet the needs of both aspects at the same time. Therefore, for applications that need to achieve both functions at the same time, the current microcapsule technology still cannot meet the requirements.

[0003] Therefore, there is an urgent need in the art for a self-healing conductive graphene-silica hybrid shell microcapsule concrete that can actively and automatically repair damaged parts and effectively solve the problems of saline soil corrosion and wind load fatigue. Summary of the invention

[0004] The purpose of the present invention is to provide a self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for transmission tower foundation and a preparation method thereof, which can actively and automatically repair damaged parts and can effectively solve the problems of saline soil corrosion and wind load fatigue.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A silicon dioxide hybrid shell microcapsule, comprising a capsule wall and a capsule core, wherein:

[0007] The capsule core comprises the following raw materials in parts by weight: 20-40 parts of microcrystalline cellulose, 1-20 parts of sodium silicate, 10-20 parts of silicate cement, 3-7 parts of magnesium oxide, 1-3 parts of methyl cellulose, 8-12 parts of methyl methacrylate monomer, and 25-33 parts of distilled water;

[0008] The capsule wall is a silica hybrid shell, which includes the following raw materials in parts by weight: 8 to 12 parts of ethyl cellulose, 8 to 12 parts of styrene, 8 to 12 parts of polyionic liquid, and 60 to 80 parts of silica fume;

[0009] The silica fume is larger than 1250 mesh and has a silicon dioxide content of more than 90%;

[0010] The surface of the capsule wall is coated with a triethyl boron coating;

[0011] The particle size of the microcapsule is 1.0 to 2.0 mm.

[0012] A self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for transmission tower foundation, comprising conductive concrete and silicon dioxide hybrid shell microcapsules, wherein:

[0013] The amount of the silica hybrid shell microcapsules is 2-3% of the total mass of the microcapsule concrete;

[0014] The conductive concrete is concrete to which a graphene oxide solution is added, and the addition amount of the graphene oxide solution is 0.05-0.25% of the total mass of the conductive concrete, and the concentration is 10 mg / ml.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. The self-repairing conductive microcapsule concrete of the present invention includes silica hybrid shell microcapsules dispersed in concrete, and the silica hybrid shell microcapsules can be broken in time when subjected to stress or corrosive ions. In addition, the silica hybrid shell microcapsules use expansion agents, adhesives, and healing agents as capsule cores. After the silica hybrid shell microcapsules are broken, the expansion agent flowing out of the core material can produce certain expansion substances to fill the cracks; the flowing adhesive and healing agent have a certain bonding effect on the cracks, and can bond the cracks to restore and restore a certain strength.

[0017] 2. The self-healing conductive graphene-silica hybrid shell microcapsule concrete of the present invention can realize intelligent self-healing function, and can be damaged in time when subjected to stress or corrosive ions. It can not only restore the strength of the material, but also fill the gaps and improve the permeability of the material to prevent the invasion of external corrosive substances.

[0018] 3. Graphene has good conductivity, durability, pressure sensitivity, and toughness, which makes concrete have good conductivity, and at the same time has good durability and corrosion resistance, preventing concrete from cracking and breaking. At the same time, the sensitive characteristics of load are conducive to the timely damage of microcapsules, which can extend the service life of buildings and structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the self-repairing structure of microcapsules when cracks are formed in concrete structure;

[0020] Figure 2 Schematic diagram of the self-healing structure of microcapsules when cracks are formed in concrete due to corrosive erosion. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0022] The present invention provides a conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for self-repairing of transmission tower foundations, wherein the microcapsule concrete comprises conductive concrete and silicon dioxide hybrid shell microcapsules, wherein:

[0023] The amount of the silica hybrid shell microcapsules is 2-3% of the total mass of the microcapsule concrete;

[0024] The conductive concrete is a concrete to which a graphene oxide solution is added, wherein the addition amount of the graphene oxide solution is 0.05-0.25% of the total mass of the conductive concrete, and the concentration is 10 mg / ml;

[0025] The silica hybrid shell microcapsule comprises a capsule wall and a capsule core, wherein: the capsule core comprises the following raw materials in parts by weight: 20-40 parts of microcrystalline cellulose, 1-20 parts of sodium silicate, 10-20 parts of silicate cement, 3-7 parts of magnesium oxide, 1-3 parts of methyl cellulose, 8-12 parts of methyl methacrylate monomer, and 25-33 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 8-12 parts of ethyl cellulose, 8-12 parts of styrene, 8-12 parts of polyionic liquid, and 50-80 parts of silica fume;

[0026] The silica fume is larger than 1250 mesh and has a silicon dioxide content of more than 90%;

[0027] The surface of the capsule wall is coated with a triethyl boron coating;

[0028] The particle size of the microcapsules is 1.0 to 2.0 mm;

[0029] The concrete is prepared from conventional concrete silicate cement, fine aggregate, coarse aggregate, water, admixtures and retarders;

[0030] The silicate cement is P·O42.5 silicate cement;

[0031] The graphene oxide solution is a 10 mg / ml industrial-grade graphene oxide solution;

[0032] The retarder is citric acid;

[0033] The organic components all have a content of 99% and are analytically pure AR.

[0034] A method for preparing the above-mentioned self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for transmission tower foundation comprises the following steps:

[0035] Step 1: Prepare the capsule core:

[0036] Step 11: Screen sodium silicate, methyl cellulose and microcrystalline cellulose, remove particles in the materials, ensure that the powders of the three are uniform in size, pour into distilled water and stir at a uniform speed until they are completely dissolved, mix the required raw materials according to the capsule core ratio, and stir until a uniform mud-like substance is formed;

[0037] Step 1 and 2, granulating and drying the muddy substance mixed in step 1 to obtain capsule core particles;

[0038] Step 2: Covering wall material:

[0039] Step 21: fully stir the required raw materials according to the capsule wall ratio to obtain a colloidal solution;

[0040] Step 22: spraying the colloidal solution on the surface of the capsule core particles so that the surface of the capsule core is completely wrapped by the capsule wall material, and placing the capsule core particles in an oven for drying to form capsule particles wrapped with the core material;

[0041] Step 23: Repeat step 22 2 to 4 times to ensure that the wall material completely covers the core material;

[0042] Step 24: sieving the particles obtained in step 23 to obtain self-repairing microcapsules;

[0043] Step 3: evenly apply triethylboron on the outer wall of the self-repairing microcapsule to obtain a silica hybrid shell microcapsule;

[0044] Step 4: Preparation of microcapsule concrete

[0045] Step 41: Pour the graphene oxide dispersion into the mixing water and mix evenly;

[0046] Step 42: Pour citric acid, the mixing water containing the graphene oxide dispersion in step 41 and silicate cement into a mixing pot, start the cement mortar mixer, stir for 30 seconds using a low speed mode, and then pour in fine aggregate and coarse aggregate;

[0047] Step 43: Stir at high speed for 30 seconds and stop stirring for 90 seconds;

[0048] Step 44: Add silica hybrid shell microcapsules, stir for 60 seconds at a low speed, then put into a mold, vibrate and cure;

[0049] Step 4 and 5: demolding is performed two days after molding to obtain self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete.

[0050] In the present invention, the functions of each raw material are as follows:

[0051] Graphene: Excellent conductivity: It has excellent conductivity. Concrete mixed with graphene has good conductivity and can be used in fields such as power transmission and sensors. High strength: It has extremely high strength. The strength of a single layer of graphene is more than 100 times that of steel. Concrete mixed with graphene has high strength and can be used in fields that require high-strength materials. Good toughness: Graphene concrete has excellent toughness and can effectively resist external shocks and vibrations. It can be used in fields that require high-toughness materials. Strong crack resistance: Graphene concrete has good crack resistance and can effectively prevent cracking and fracture of concrete. Excellent pressure-sensitive properties: Graphene concrete has pressure-sensitive properties, which can realize sensitive monitoring of loads and is used for health monitoring and early warning of building structures. Good durability: Graphene concrete has good durability and corrosion resistance, which can extend the service life of buildings and structures.

[0052] Ethyl cellulose: water retaining agent and stabilizer, used for coating materials to make sustained-release capsules, with relatively stable chemical properties and good film-forming properties: Ethyl cellulose has good film-forming properties and can form a uniform and complete wall material layer on the surface of silica ash to ensure the sealing and protective properties of the microcapsule wall material; has excellent mechanical properties: Ethyl cellulose has high mechanical strength and toughness, can withstand a certain amount of pressure and tension, and ensure that the microcapsules are not easy to break or deform during the application process, thereby increasing the service life of the self-healing microcapsules; easy to prepare: Ethyl cellulose is a commonly used polymer material.

[0053] Silica fume: It can absorb organic matter on its surface, so that the microcapsule silica hybrid shell has a certain strength and remains brittle, and it will break in time when subjected to stress to release the core material.

[0054] Styrene and polyionic liquid: Styrene and polyionic liquid are cross-linked to form a hydrophobic shell. After the polyionic liquid on the surface "senses" the corrosive ions, the polyionic liquid and the corrosive ions are replaced, and the hydrophobic shell forms a hydrophilic channel. At the same time, the core material reacts with the solution to affect the viscosity of the solution.

[0055] Sodium silicate: It has strong bonding properties and resistance to high temperature and chemical corrosion. It is acid-resistant, heat-resistant, dense and impermeable, low-priced and easy to use. It is an excellent adhesive and sealant. When sodium silicate comes into contact with cement-based materials and reacts under the action of water, the silicate ions in the sodium silicate and the calcium ions in the cement will combine to form a solid product. This product can fill water to bond the concrete on both sides, thereby enhancing the strength and durability of the cement. It will react with calcium hydroxide as follows:

[0056] Na2SiO3+Ca(OH)2=CaSiO3↓+2NaOH.

[0057] Magnesium oxide: It generates magnesium hydroxide when it comes into contact with water, so it has good expansibility and water absorption. It can expand several times in water or water-based liquids, allowing the microcapsules to expand rapidly in a wet environment. Therefore, as long as the appropriate ratio can be determined, the requirements for the core material's expansibility can be met, thereby achieving the repair function.

[0058] Microcrystalline cellulose and methyl cellulose: Microcrystalline cellulose is a product synthesized from cellulose and can act as an excipient and disintegrant. Methyl cellulose is a product synthesized from cellulose and has thickening, surface activity and film-forming functions. The two components work together to adjust the shape of the core material to meet the needs of later processing.

[0059] Methyl methacrylate monomer and triethylboron: When damaged by stress or corrosive ions, the microcapsules are expected to rupture due to crack propagation, thereby releasing the healing agent methyl methacrylate monomer, which fills the cracks by capillary action. When the healing agent contacts the surface coating catalyst triethylboron through the ruptured microcapsules, its polymerization is triggered, bonding the crack surfaces together. The polymerization reaction of methyl methacrylate monomer initiated by triethylboron at room temperature is as follows:

[0060]

[0061] Embodiment 1:

[0062] In this embodiment, microcapsule concrete is prepared from silica hybrid shell microcapsules and conductive concrete, wherein:

[0063] The conductive concrete is a concrete with graphene oxide solution added, wherein: the concrete adopts C30 concrete raw materials of a commercial concrete company in the 750kV power transmission and transformation project in Lanlin, Gansu: 236kg of silicate cement, 865kg of fine aggregate, 865kg of coarse aggregate, 180kg of water, 10.3kg of admixture, and 4kg of retarder. It can be seen from Table 1 that the cost performance is the highest when 0.1% of graphene oxide solution is added. The addition amount of the microcapsule is 2%, and its strength is shown in Table 2.

[0064] Table 1 Effect of adding 10 mg / ml industrial-grade graphene oxide solution on concrete strength and typical

[0065]

[0066] Table 2

[0067]

[0068] The silica hybrid shell microcapsule comprises a capsule wall and a capsule core, wherein: the capsule core comprises the following raw materials in parts by weight: 30 parts of microcrystalline cellulose, 15 parts of sodium silicate, 15 parts of silicate cement, 5 parts of magnesium oxide, 2 parts of methyl cellulose, 9 parts of methyl methacrylate monomer, and 29 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 10 parts of ethyl cellulose, 10 parts of styrene, 10 parts of polyionic liquid, and 70 parts of silica fume.

[0069] The specific preparation steps are as follows:

[0070] Step (1) Mixing the core material: First, use a 0.5 mm square hole sieve to screen sodium silicate, methyl cellulose and microcrystalline cellulose to remove particles in the materials and ensure that the powder particle size of the three is uniform. Pour into distilled water and stir at a constant speed at a temperature of 40° until completely dissolved. Then, according to the core material ratio, mix the required materials and stir until a uniform mud-like substance is formed.

[0071] Step (2) making the core material: the mixed raw materials are placed in a manual granulation device, and the granulator is started to rotate at a certain speed. Under the action of stirring and extrusion, the core material raw materials are compressed into a corresponding shape and then extruded through a small hole with a radius of 1 mm. These extruded core material particles are cut into appropriate sizes and shapes to form light yellow, slightly moist small balls. These small balls are placed in a drying oven and dried at a constant temperature of 45°C for 12 hours to finally obtain core material particles.

[0072] Step (3) Covering the wall material: First, the capsule wall material needs to be mixed and stirred thoroughly to obtain a colloidal solution. Next, use a spray bottle to spray small droplets of the solution on the surface of the core material particles so that the surface of the core material is completely covered by the capsule wall material. Then, put these particles into a drying oven and dry them at 50°C for 4 hours to ensure that the capsule wall material is completely dry. Under the action of hot air, the moisture in the capsule shell evaporates rapidly, causing the droplets to dry quickly to form capsule particles that wrap the core material. Repeat this process three times to ensure that the wall material completely wraps the core material. Finally, use a square hole sieve to screen the obtained gray particles to obtain self-healing microcapsules with a particle size between 1.0 and 2.0 mm. Finally, the outer wall of the self-healing microcapsule is evenly coated with triethyl boron.

[0073] Step (4) concrete: pour the graphene oxide dispersion into the mixing water in advance to mix evenly, then pour citric acid, mixing water, admixture and cement into the mixing pot respectively, place the mixing pot on a fixed frame, adjust the height of the mixing pot, start the cement mortar mixer, stir for 30 seconds in low speed mode, and then pour in the aggregate. Stir for 30 seconds in high speed mode, stop stirring for 90 seconds, and finally add the microcapsules, stir for 60 seconds in low speed mode, put into the mold, vibrate and maintain. It should be noted that citric acid is poured into the mixing pot together with water, and the microcapsules are added after the above stirring process is completed, so as to prevent the microcapsules from breaking during stirring. Because citric acid has the characteristics of slow setting, for concrete, the demoulding time of the specimen is changed to two days after molding, so as to ensure that the cement inside the specimen is fully solidified and avoid deformation or damage of the specimen during demoulding.

[0074] like Figure 1 and Figure 2 As shown, cracks are formed in concrete structures ( Figure 1 ) or corrosive ion erosion ( Figure 2 ), the capsule wall is stressed or eroded and damaged, causing the capsule core to disperse outside the capsule, and the following will happen: ① Sodium silicate reacts with calcium ions free in water in concrete to generate calcium carbonate, thereby repairing cracks; ② Magnesium oxide generates magnesium hydroxide when it comes into contact with water or a humid environment, which has good swelling and water absorption properties, thereby achieving the repair function; ③ When the methyl methacrylate monomer comes into contact with the surface coating triethylboron through the broken microcapsules, its polymerization is triggered, bonding the crack surfaces together, thereby repairing the cracks.

[0075] Embodiment 2:

[0076] This embodiment is different from Embodiment 1 in that the capsule core comprises the following raw materials in parts by weight: 25 parts of microcrystalline cellulose, 20 parts of sodium silicate, 12 parts of silicate cement, 7 parts of magnesium oxide, 2 parts of methyl cellulose, 10 parts of methyl methacrylate monomer, and 29 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 8 parts of ethyl cellulose, 8 parts of styrene, 8 parts of polyionic liquid, and 76 parts of silica fume.

[0077] Embodiment 3:

[0078] This embodiment is different from Embodiment 1 in that the capsule core comprises the following raw materials in parts by weight: 35 parts of microcrystalline cellulose, 10 parts of sodium silicate, 17 parts of silicate cement, 5 parts of magnesium oxide, 2 parts of methyl cellulose, 7 parts of methyl methacrylate monomer, and 29 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 12 parts of ethyl cellulose, 12 parts of styrene, 12 parts of polyionic liquid, and 54 parts of silica fume.

Claims

1. A silica hybrid shell microcapsule, comprising a capsule wall and a capsule core, characterized in that The capsule core comprises the following raw materials in parts by weight: 20-40 parts of microcrystalline cellulose, 1-20 parts of sodium silicate, 10-20 parts of silicate cement, 3-7 parts of magnesium oxide, 1-3 parts of methyl cellulose, 8-12 parts of methyl methacrylate monomer, and 25-33 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 8-12 parts of ethyl cellulose, 8-12 parts of styrene, 8-12 parts of polyionic liquid, and 60-80 parts of silica fume; and the surface of the capsule wall is coated with a triethyl boron coating.

2. The silica hybrid shell microcapsule according to claim 1, characterized in that The silica fume has a mesh size of 1250 or more and a silicon dioxide content of more than 90%.

3. The silica hybrid shell microcapsule according to claim 1, characterized in that The particle size of the microcapsule is 1.0 to 2.0 mm.

4. A self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for transmission tower foundation, characterized in that The microcapsule concrete comprises conductive concrete and silica hybrid shell microcapsules, wherein: The amount of the silica hybrid shell microcapsules is 2-3% of the total mass of the microcapsule concrete; The conductive concrete is a concrete to which a graphene oxide solution is added, and the addition amount of the graphene oxide solution is 0.05 to 0.25% of the total mass of the conductive concrete; The silica hybrid shell microcapsule comprises a capsule wall and a capsule core, wherein the capsule core comprises the following raw materials in parts by weight: 20 to 40 parts of microcrystalline cellulose, 1 to 20 parts of sodium silicate, 10 to 20 parts of silicate cement, 3 to 7 parts of magnesium oxide, 1 to 3 parts of methyl cellulose, 8 to 12 parts of methyl methacrylate monomer, and 25 to 33 parts of distilled water; the capsule wall is a silica hybrid shell, comprising the following raw materials in parts by weight: 8 to 12 parts of ethyl cellulose, 8 to 12 parts of styrene, 8 to 12 parts of polyionic liquid, and 60 to 80 parts of silica fume; and the surface of the capsule wall is coated with a triethyl boron coating.

5. The conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for self-repairing of transmission tower foundation according to claim 4 is characterized in that The silica fume has a mesh size of 1250 or more and a silicon dioxide content of more than 90%.

6. The conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for self-repairing of transmission tower foundation according to claim 4, characterized in that The particle size of the silicon dioxide hybrid shell microcapsule is 1.0 to 2.0 mm.

7. The conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for self-repairing of transmission tower foundation according to claim 4, characterized in that The concentration of the graphene oxide solution is 10 mg / ml.

8. A method for preparing the self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete suitable for transmission tower foundations according to any one of claims 4 to 7, characterized in that The method comprises the following steps: Step 1: Prepare the capsule core: Step 11: Screen sodium silicate, methyl cellulose and microcrystalline cellulose, remove particles in the materials, ensure that the powders of the three are uniform in size, pour into distilled water and stir at a uniform speed until they are completely dissolved, mix the required raw materials according to the capsule core ratio, and stir until a uniform mud-like substance is formed; Step 1 and 2, granulating and drying the muddy substance mixed in step 1 to obtain capsule core particles; Step 2: Covering wall material: Step 21: fully stir the required raw materials according to the capsule wall ratio to obtain a colloidal solution; Step 22: spraying the colloidal solution on the surface of the capsule core particles so that the surface of the capsule core is completely wrapped by the capsule wall material, and placing the capsule core particles in an oven for drying to form capsule particles wrapped with the core material; Step 23: Repeat step 22 2 to 4 times to ensure that the wall material completely covers the core material; Step 24: sieving the particles obtained in step 23 to obtain self-repairing microcapsules; Step 3: evenly apply triethylboron on the outer wall of the self-repairing microcapsule to obtain a silica hybrid shell microcapsule; Step 4: Preparation of microcapsule concrete Step 41: Pour the graphene oxide dispersion into the mixing water and mix evenly; Step 42: Pour citric acid, the mixing water containing the graphene oxide dispersion in step 41 and silicate cement into a mixing pot, start the cement mortar mixer, stir for 30 seconds using a low speed mode, and then pour in fine aggregate and coarse aggregate; Step 43: Stir at high speed for 30 seconds and stop stirring for 90 seconds; Step 44: Add silica hybrid shell microcapsules, stir for 60 seconds at a low speed, then put into a mold, vibrate and cure; Step 4 and 5: demolding is performed two days after molding to obtain self-repairing conductive graphene-silicon dioxide hybrid shell microcapsule concrete.